Redescription of Lutzomyia (Lutzomyia) renei Martins, Falcão & Silva, 1957 (Diptera: Psychodidae: Phlebotominae) - Sábio, Priscila B.; Andrade, Andrey J. De; Galati, Eunice A. B. (Zootaxa, 2015)
The male genitalia of Lutzomyia (Lutzomyia) renei (Martins, Falcão & Silva, 1957) have four bristles, three fine and one semi-foliaceous, inserted basomesally on the gonocoxite. Nonetheless, in the original description and in other taxonomic studies, these bristles have been illustrated and described in varying formats. In order to clarify the morphology of this species, both sexes are here redescribed based on three males and one female from the type series. A lectotype and two paralectotypes are here designated.